Product Image And Ethnocentrism Factors In Influencing Knowledge Of UIS Karo Among Universitas Medan Area Students - Lubis, Adelina; Siti Anggiani Syahvira; Aulia Sofiea Putri; Zul Azmi Mutahajjid; Lubis, Andi Reza Syahputra (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This study aims to analyze the influence of product image and ethnocentrism factors on knowledge about Uis Karo, a traditional cloth typical of the Karo people, among students of Medan Area University. Product image refers to students' perceptions of the quality, beauty, and relevance of Uis Karo as part of local culture, while ethnocentrism refers to the tendency to prioritize and value local products over foreign products. The research method uses a quantitative approach with data collection through questionnaires distributed to 98 students. The results of the analysis show that product image has a significant influence on students' knowledge of Uis Karo, where positive perceptions of the quality and aesthetics of Uis Karo increase students' interest in learning about this cultural product. In addition, ethnocentrism factors have also been shown to have a significant influence; students with high levels of ethnocentrism tend to be more interested and have better knowledge about Uis Karo. These findings imply the importance of promotional strategies that strengthen the image of Uis Karo products and strengthen ethnocentrism attitudes to increase understanding and pride in local culture among the younger generation.